The sound around: ambiences, affects and audio technologies in “Penny Lane” - Martoni, Alex (2015)
This paper aims to understand how the material dimension of vocal performance and audio recordings and reproductions influences the process of building a kind of sensory experience that we usually call atmosphere, mood or ambience. Within this perspective, we will focus on the song “Penny Lane”, by the Beatles, in order to think of the inflexions of the technique in the realm of the affections, as well as the way we attribute senses when we listen to a song and also in the realm of cultural experience of listening.